Practical approach to tachyarrhythmia in children. Issue 12 (December 2022) - Yap, Norah YS.; Yue, Arthur; Sadagopan, Shankar; Hayes, Nicholas
Abstract: Abnormalities of the cardiac rhythm are relatively common in children, with an estimated incidence of almost 1 in 4000 births. Most of these are supraventricular, and about half of children will experience their first episode as an infant. Symptoms, particularly in younger children, may be hard to detect. Delay in diagnosis can lead to ventricular dysfunction, heart failure and acute collapse. This short review provides an overview of the types of cardiac arrhythmias commonly encountered in children, provides practical advice for diagnosis, including the utility of different types of cardiac monitoring devices and outlines the management options.